1.
Evaluate the given expression where a=2, b=4 and c=8:
(((++a)!=8) || (--b==8))
Correct Answer
A. True
Explanation
The given expression (((++a)!=8) || (--b==8)) is evaluated as follows:
- (++a) increments the value of a by 1, so a becomes 3.
- The expression (++a)!=8 evaluates to true because 3 is not equal to 8.
- (--b) decrements the value of b by 1, so b becomes 3.
- The expression (--b==8) evaluates to false because 3 is not equal to 8.
- The logical OR operator (||) returns true if at least one of the expressions on either side is true.
- Since the first expression is true, the overall expression evaluates to true.
2.
Evaluate the given expression where a=2, b=4 and c=8:((c++) !=5 ^ (--a==6))
Correct Answer
A. True
Explanation
The given expression is evaluated as follows:
1. The value of c++ is 8 (post-increment), which is not equal to 5.
2. The value of a is decremented by 1 (pre-decrement), which becomes 1.
3. Since 1 is not equal to 6, the expression (--a==6) evaluates to False.
4. The != operator compares the result of step 1 (True) with the result of step 3 (False), which gives True.
Therefore, the correct answer is True.
3.
Evaluate the given expression where a=2, b=4 and c=8:
!(((--a)!=4) && (++b!=2))
Correct Answer
B. False
Explanation
The expression is evaluating whether the statement inside the parentheses is true or false. The statement inside the parentheses is "!(((--a)!=4) && (++b!=2))".
First, "--a" decrements the value of "a" by 1, so "a" becomes 1. Next, "++b" increments the value of "b" by 1, so "b" becomes 5.
Then, "a!=4" evaluates to true because 1 is not equal to 4. Similarly, "b!=2" evaluates to true because 5 is not equal to 2.
The "&&" operator checks if both statements are true, and since they are, the result is true. Finally, the "!" operator negates the result, making it false. Therefore, the correct answer is false.
4.
Evaluate the given expression where a=2, b=4 and c=8:
(c++ !=b) || (a++==b)
Correct Answer
A. True
Explanation
The given expression is a logical OR operation between two sub-expressions. In the first sub-expression, (c++ != b), the value of c is incremented by 1 after the comparison, resulting in c=9. Since 9 is not equal to b=4, the first sub-expression evaluates to true. In the second sub-expression, (a++ == b), the value of a is incremented by 1 after the comparison, resulting in a=3. Since 3 is equal to b=4, the second sub-expression evaluates to true. Since the logical OR operator returns true if at least one of the sub-expressions is true, the overall expression evaluates to true.
5.
Evaluate the given expression where a=2, b=4 and c=8:
!(((++a)!=2) ^ (--b==2))
Correct Answer
B. False
Explanation
The given expression is a logical expression that involves the increment and decrement operators. The expression first increments the value of 'a' by 1 (++a), then checks if it is not equal to 2. If it is not equal to 2, the expression inside the first set of parentheses evaluates to true. The expression also decrements the value of 'b' by 1 (--b), then checks if it is equal to 2. If it is equal to 2, the expression inside the second set of parentheses evaluates to true. Finally, the two expressions inside the parentheses are combined with the XOR operator (^). Since one expression is true and the other is false, the result of the XOR operation is true. However, the entire expression is negated by the NOT operator (!), resulting in the final answer of false.
6.
Evaluate the given expression where a=16, b=4 and c=8:
b+c > a
Correct Answer
B. False
Explanation
The expression "b+c > a" is evaluating whether the sum of b and c is greater than a. In this case, b is 4 and c is 8, so their sum is 12. However, a is 16. Since 12 is not greater than 16, the expression "b+c > a" is false.
7.
Evaluate the given expression where a=16, b=4 and c=8:
C*b == a
Correct Answer
A. True
Explanation
The given expression is "C*b == a". We are given that a=16, b=4, and c=8. Plugging in these values, we get 8*4 == 16. This simplifies to 32 == 16. Since 32 is not equal to 16, the expression is false. Therefore, the correct answer is False.
8.
Evaluate the given expression where a=16, b=4 and c=8:
a/b != c
Correct Answer
B. False
Explanation
The given expression is "a/b != c", where a = 16, b = 4, and c = 8.
Substituting the values, we get 16/4 != 8.
Simplifying further, we have 4 != 8.
Since 4 is not equal to 8, the expression is true.
Therefore, the correct answer is False.
9.
Evaluate the given expression where a=16, b=4 and c=8:
a/5+5 <= ++c*b-5
Correct Answer
B. False
Explanation
The given expression is a/5+5
10.
Evaluate the given expression where a=16, b=4 and c=8:
-b*a <= a
Correct Answer
A. True
Explanation
The given expression is "-b*a
11.
Evaluate the given expression where a=16, b=4 and c=8:
(c++!=b) || (a++==b)
Correct Answer
A. True
Explanation
The given expression is a logical OR operation between two sub-expressions. In the first sub-expression, c++ is incremented by 1 and then compared to b. Since c is initially 8 and b is 4, the comparison evaluates to true. In the second sub-expression, a is compared to b. Since a is initially 16 and b is 4, the comparison evaluates to false. Since it is a logical OR operation, if any of the sub-expressions evaluate to true, the overall expression evaluates to true. Therefore, the correct answer is True.
12.
Evaluate the given expression where a=16, b=4 and c=8:
!(((++a)!=4) && (--b==4))
Correct Answer
A. True
Explanation
The given expression is evaluating the logical NOT operator (!) applied to the logical AND operator (&&) between two sub-expressions. In the first sub-expression, (++a) increments the value of 'a' by 1 and checks if it is not equal to 4. Since 'a' is initially 16, the incremented value is 17, which is not equal to 4. Therefore, the first sub-expression evaluates to true. In the second sub-expression, (--b) decrements the value of 'b' by 1 and checks if it is equal to 4. Since 'b' is initially 4, the decremented value is 3, which is not equal to 4. Therefore, the second sub-expression evaluates to false. Since both sub-expressions are connected by the logical AND operator, both sub-expressions must be true for the overall expression to be true. However, since the second sub-expression is false, the overall expression evaluates to false. Therefore, the correct answer should be False, not True.
13.
Evaluate the given expression where a=16, b=4 and c=8:
(b>b) ^ (a++==c)
Correct Answer
A. True
Explanation
The expression (b>b) ^ (a++==c) can be evaluated as follows:
- First, the subexpression (b>b) evaluates to False, as 4 is not greater than 4.
- Next, the subexpression (a++==c) evaluates to True, as the value of a (16) is equal to c (8) and then a is incremented by 1.
- Finally, the XOR (^) operator is applied to False and True, resulting in True. Therefore, the correct answer is True.
14.
Evaluate the given expression where a=16, b=4 and c=8:
!((c--==b) || (a++>b*c))
Correct Answer
B. False
Explanation
The given expression is evaluating the logical NOT of a compound condition. The first part of the condition checks if the value of c decremented by 1 is equal to b. Since c is initially 8 and is decremented to 7, and b is 4, the condition is false. The second part of the condition checks if the bitwise AND of a incremented by 1 and b multiplied by c is true. Since a is initially 16 and is incremented to 17, and b is 4 and c is 8, the condition is false. Since both parts of the condition are false, the overall expression is true.
15.
Evaluate the given expression where a=16, b=4 and c=8:
(c*b==a) ^ (--b*a<=a)
Correct Answer
B. False
Explanation
The given expression evaluates to False. The first part of the expression, (c*b==a), checks if the product of c and b is equal to a, which is not true since 8 multiplied by 4 is 32, not 16. The second part of the expression, (--b*a
16.
Evaluate the given expression where a=16, b=4 and c=8:
(c++!=b) && (a++==b)
Correct Answer
B. False
Explanation
The given expression consists of two conditions joined by the logical AND operator. In the first condition, (c++!=b), the value of c is incremented by 1 and then compared to b. Since the value of c is 8 and b is 4, the condition evaluates to true. In the second condition, (a++==b), the value of a is compared to b and then incremented by 1. Since the value of a is 16 and b is 4, the condition evaluates to false. Since both conditions need to be true for the logical AND operator to return true, the overall expression evaluates to false.
17.
Evaluate the given expression where a=16, b=4 and c=8:
(a==b*4) ^ (c++==a)
Correct Answer
A. True
Explanation
The given expression consists of two parts connected by the XOR operator (^). In the first part, it checks if a is equal to b multiplied by 4. Since a is 16 and b is 4, the expression evaluates to true. In the second part, it checks if c incremented by 1 is equal to a. Since c is 8 and a is 16, the expression evaluates to false. Finally, the XOR operator returns true if either of the two parts is true, but not both. Therefore, the overall expression evaluates to true.
18.
Evaluate the given expression where a=16, b=4 and c=8:
(c*b!=a) || (b*a<=a)
Correct Answer
B. False
Explanation
The given expression consists of two parts connected by the logical OR operator. In the first part, (c*b!=a), we check if the product of c and b is not equal to a. Since c=8 and b=4, their product is 32, which is not equal to a=16. Therefore, the first part of the expression evaluates to true. In the second part, (b*a
19.
Evaluate the given expression where a=16, b=4 and c=8:
!((++a!=4) || (--b==4))
Correct Answer
B. False
Explanation
The given expression is evaluating the logical expression inside the parentheses, which is "++a!=4". Here, "++a" increments the value of "a" by 1, resulting in "a" being equal to 17. Then, the expression checks if "a" is not equal to 4, which is true. The logical expression after the "||" operator is "--b==4". Here, "--b" decrements the value of "b" by 1, making it equal to 3. The expression then checks if "b" is equal to 4, which is false. Since the logical OR operator is used between these two expressions, the overall result is false.
20.
Evaluate the given expression where a=16, b=4 and c=8:
(b+b*b==a) && (c*b==a)
Correct Answer
B. False
Explanation
The given expression is evaluating whether the statement (b+b*b==a) is true and whether the statement (c*b==a) is true. In this case, b=4 and a=16, so the first statement becomes (4+4*4==16), which simplifies to (4+16==16), which is false. Therefore, the overall expression evaluates to false.
21.
Evaluate the given expression where a=16, b=4 and c=8:
b+=4 == 10
Correct Answer
B. False
Explanation
The given expression is b+=4 == 10. Here, b+=4 means adding 4 to the current value of b and assigning the result back to b. So, b+=4 == 10 can be rewritten as b = b + 4, and then checking if b is equal to 10. Given that b=4, adding 4 to it would result in b=8, which is not equal to 10. Therefore, the expression b+=4 == 10 evaluates to False.
22.
Evaluate the given expression where a=16, b=4 and c=8:
(c*=2) != a
Correct Answer
B. False
Explanation
The given expression is (c*=2) != a. In this expression, the value of c is multiplied by 2, which means c becomes 16. Then, the expression checks if c is not equal to a. Since c is equal to a (both are 16), the expression evaluates to False.
23.
Evaluate the given expression where a=16, b=4 and c=8:
(a/=2) == c
Correct Answer
A. True
Explanation
The given expression (a/=2) == c can be evaluated as follows: a divided by 2 is equal to 8, and 8 is equal to c. Therefore, the expression is true.
24.
Evaluate the given expression where a=16, b=4 and c=8:
(c%=b) != a
Correct Answer
A. True
Explanation
The expression evaluates whether the remainder of dividing c by b is not equal to a. In this case, c divided by b gives a remainder of 0, which is not equal to a. Therefore, the expression is true.
25.
Evaluate the given expression where a=16, b=4 and c=8:
(a-=c) == (c*=2)
Correct Answer
B. False
Explanation
The given expression (a-=c) == (c*=2) is evaluating whether the value of (a minus equal c) is equal to the value of (c multiplied equal to 2). In other words, it is checking if the result of subtracting c from a is equal to the result of multiplying c by 2. In this case, a is initially 16, c is 8, and b is 4. Therefore, (a-=c) is equivalent to (16-8), which is 8. And (c*=2) is equivalent to (8*2), which is 16. Since 8 is not equal to 16, the expression evaluates to False.